Properties of Asphalt Concrete Containing Waste Foundry Sand (WFS) as Filler Material - Shuaibu, A. A.; Otuoze, H. S.; Mohammed, A.; Lateef, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The high cost of primary construction materials such as cement, and increase in waste generation due to human activities coupled with environmental concerns has led to the incorporation of wide range of waste materials into asphalt concrete. Waste foundry sand (WFS) which is a by-product of ferrous and non-ferrous metal casting industry, has accumulated in stockpiles and landfills, occupying valuable space and causing nuisance in the environment. Consequently, it is imperative to devise a safe and economical solution to manage and utilize the waste. One way of achieving this is by recycling and using it for asphalt concrete production. This study investigated the strength and durability properties of asphalt concrete containing waste foundry sand (WFS) as alternative filler material in asphalt concrete. Marshall design method was adopted for the sample preparation and testing. Fifteen (15) compacted samples were prepared for strength and volumetric properties testing at varying bitumen contents of 4.5%, 5.0%, 5.5%, 6.0% and 6.5%, in accordance with Asphalt Institute and Nigeria General Specification for Road and Bridges to determine optimum bitumen content (OBC). OBC of 5.5% was obtained and used for the asphalt concrete mixes in the study.  Eighteen (18) other briquettes were prepared to determine the optimum WFS content in asphalt concrete necessary for strength and durability of wearing course of flexible pavement. Cement as filler in asphalt concrete was partially replaced with WFS using the obtained OBC in the order of 10%, 20%, 30%, 40%, 50% and 60%. A total of thirty-three (33) standard specimens were prepared. From the Marshall stability-flow and void-density results, the sample prepared with 60% WFS as filler with OBC of 5.5% satisfies the provision of the Nigerian General Specification for Road and Bridges (NGSRB) for use in wearing course of flexible pavement. Based on the analysis of results obtained in this study and a logical comparison made with standard specifications, addition of up to 60% waste foundry sand (WFS) in asphalt concrete would lead to significant conservation of primary construction materials, divert substantial quantities of waste from landfills and present a cheap alternative of filler material necessary for sustainable asphalt concrete construction.